Modulation of 5-ALA Fluorescence and ABCG2 Response by Ultrasound in Glioma. (16th November 2020) - Yamaguchi, Fumio; Higuchi, Tadashi; Asakura, Takayuki; Yoshida, Daizo; Oiso, Yumiko; Morita, Akio
Abstract: INTRODUCTION: 5-Aminolevulinic Acid (5-ALA) Photodiagnosis is an effective method to detect residual tumors during glioma surgery. However, the strength of fluorescence differs in every case even in the most malignant glioma such as glioblastoma. Also, negative false-negative fluorescence may result in tumor residue. METHODS: The malignant glioma established cell line, SNB19, U87MG and T98G were used for in vitro experiments. Ultrasound (1MHz, 3W/cm 2, Duty cycle 10%) was irradiated on the cultured cells after administration of 5-ALA. The morphological changes of tumor cells were observed. The PpIX levels and the expression of ABCG2 were evaluated. RESULTS: The glioma tumor cells showed transient morphological changes and attachment to the culture dish, while most cells survived and were restored to their original morphology within 6 hours. The PpIX expression levels increased in glioma cells after ultrasound irradiation, earlier and higher than 5-ALA alone. Concurrently the expressions of ABCG2, that increased after 5-ALA administration, were relatively reduced in ultrasound irradiated glioma cells. CONCLUSION: The ultrasound irradiation of the malignant gliomas contributes to the stronger 5-ALA induced fluorescence by elevating intracellular PpIX levels. The suppression of ABCG2 expression by ultrasound may be one of the factors which contributes to the PpIX accumulation in glioma cells.